1998
DOI: 10.1063/1.1148946
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and versatile torque magnetometer for use in high magnetic fields

Abstract: We describe the design and construction of a sensitive dc torque magnetometer suitable for liquid as well as solid state samples. It can be used from room temperature down to very low temperatures (mK range) in magnetic fields produced either by superconducting or resistive magnets, in particular in the high fields (B≈30 T) produced by Bitter and hybrid magnets. The highest resolution that we have attained so far is about 0.3 pNm, which is mainly the result of a symmetric design. In typical laboratory conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Wiegers et al [11] described a magnetometer whose design was optimized for low coupling to external sources of vibration. It consisted ( figure 1(c)) of a 17.6 mm diameter, hollow, lightweight cylindrical rotor with eight capacitance electrodes evenly spaced around its outer diameter, and the 3 by 5 mm sample mounted on a platform at its centre.…”
Section: Torsion-balance Magnetometersmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiegers et al [11] described a magnetometer whose design was optimized for low coupling to external sources of vibration. It consisted ( figure 1(c)) of a 17.6 mm diameter, hollow, lightweight cylindrical rotor with eight capacitance electrodes evenly spaced around its outer diameter, and the 3 by 5 mm sample mounted on a platform at its centre.…”
Section: Torsion-balance Magnetometersmentioning
confidence: 99%
“…A plastic disc was mounted on the fibre with its face perpendicular to the fibre. On one side of the disc a semicircular capacitance electrode was evaporated, and electrically Schematic diagrams of the magnetometers of: (a) Eisenstein et al [6]; (b) Templeton [10]; (c) Wiegers et al [11]; (d) Matthews et al [12]; (e) Schaapman et al [13]; (f) Schwarz et al [14]. The magnetic field direction in (a) and (c) to (f) is vertical; in (b) it is horizontal.…”
Section: Torsion-balance Magnetometersmentioning
confidence: 99%
“…These design features have reduced a parasitic link coupling with external vibrations. The resonant frequency of the suspended system is 1.5Hz, and the sensitivity threshold of this magnetometer can be estimated from the reported measurements of the oscillatory signal as δm ∼ 0.01µ B per electron, although slow variations of the background were a factor of 10 larger [12,13]. The authors estimated the threshold magnetometer sensitivity as 10 −13 J/Tesla, which is equivalent to δM = 10 10 Bohr magneton in field of 1 T.…”
Section: Torsion Magnetometers With Electric Detectionmentioning
confidence: 99%
“…The magnetometer employed is modeled after a design by Wiegers et al 8 , with modifications for simultaneous transport measurement and is shown in the inset of figure 1.…”
Section: Equilibrium Magnetization Measurements Manifested By the Wementioning
confidence: 99%